2012
DOI: 10.5152/balkanmedj.2011.017
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Results of Aortic Valve Replacement with Cryopreserved Homografts

Abstract: Objective: The aim of this study was to analyze the midterm clinical results of aortic valve replacement with cryopreserved homografts.Materials and Methods: Aortic valve replacement was performed in 40 patients with cryopreserved homograft. The indications were aortic valve endocarditis in 20 patients (50%), truncus arteriosus in 6 patients (15%), and re-stenosis or regurtitation after aortic valve reconstruction in 14 (35%) patients. The valve sizes ranged from 10 to 27mm. A full root replacement technique w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A possible explanation is that the indication for using allografts for AVR has changed over time from a broad range of patients to mostly complex patients with active endocarditis [ 4 , 6 ]. Indeed, in this review, three relatively recent studies with endocarditis as indication for surgery in more than 40% of the patients reported relatively high early mortality risks [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that the indication for using allografts for AVR has changed over time from a broad range of patients to mostly complex patients with active endocarditis [ 4 , 6 ]. Indeed, in this review, three relatively recent studies with endocarditis as indication for surgery in more than 40% of the patients reported relatively high early mortality risks [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can also explain why the late mortality rate is lower in studies on allografts with a more recent implantation period; in recent years, the indication for using allografts for AVR is often endocarditis [ 4 , 6 ]. Indeed, three relatively recent studies in this review, where the indication for surgery was endocarditis in more than 40% of the patients, reported relatively low late mortality rates [ 23 25 ]. Furthermore, the low mean age of two studies with a high proportion of concomitant procedures [ 33 , 34 ] might explain why studies with a high proportion of concomitant procedures report lower late mortality rates.…”
Section: Discussionmentioning
confidence: 99%